Analysis of factors influence on the operator’s psychophysiological state diagnostics quality - Булыгина, Елена Вячеславовна (Technology audit and production reserves, 2014)
System analysis of the factors, influencing the quality of measurement and diagnosing when studying the cerebral cortex biorhythms using EEG was conducted in the paper. The main purpose of the paper is taking note of the impact of factors, increasing the diagnostics reliability of operator’s psychophysiological state. Based on the standard procedures for using EEG, the influence of the key factors and their components on the operator’s psychophysiological state diagnostics was considered. These include factors, characterizing the research object, expert’s qualifications, measurement channel design, as well as information processing methods, which were the objects of the conducted classification analysis. It was found that these factors do not have an analytic representation that leads to the subjectivism in diagnostic inference. To eliminate subjectivism and increase the operator’s psychophysiological state diagnostics reliability, using quantitative integral parameter, equivalent to the biorhythm energy and associated with the electroencephalogram result, was proposed. This integral parameter can be used for estimating the professional aptitude of operators, whose work is connected with the necessity of mobilization and concentration of psychophysiological features.